2014
DOI: 10.1007/s10597-014-9769-9
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of Young People to Their Experiences of First-Episode Psychosis: Harnessing Resilience

Abstract: There is a burgeoning literature on first-episode psychosis, the focus of which is early intervention. Little emphasis has been placed on the responses of young people to their experiences of psychosis. This study, therefore, aimed to describe and explain the responses of young people to their first episode of psychosis. Data obtained from ten young people who attended a community early intervention recovery program in Perth Western Australia were analysed using a grounded theory method. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In one exception to the dominance of quantitative research work in this area, a study which aimed to explore experiences of first episode of psychosis used a qualitative design and methodology. A key finding from this study was that the ability to self-pace and feel in control over aspects of their mental health problems helped participants to counter relapse and the worsening of symptoms which the authors labeled as a resilience mechanism (Henderson & Cock, 2015). However, the goal of the study by Hwas not to explore psychological resilience.…”
Section: Introductionmentioning
confidence: 93%
“…In one exception to the dominance of quantitative research work in this area, a study which aimed to explore experiences of first episode of psychosis used a qualitative design and methodology. A key finding from this study was that the ability to self-pace and feel in control over aspects of their mental health problems helped participants to counter relapse and the worsening of symptoms which the authors labeled as a resilience mechanism (Henderson & Cock, 2015). However, the goal of the study by Hwas not to explore psychological resilience.…”
Section: Introductionmentioning
confidence: 93%
“…Southwick et al () suggest that social support may be related to resilience through a number of intermediary mechanisms, such as the motivation to reduce risky behaviours. In a qualitative study examining individuals' experience of first‐episode psychosis, Henderson and Cock () identified two types of resilience: “Tenacity,” which involved the input of effort over time, and “Rebounding,” meaning springing back or continuing with life. Self‐esteem, quality of life and spirituality also positively correlated with higher scores on a self‐report scale of psychological resilience in patients with schizophrenia and bipolar disorder (BD; Mizuno et al, ).…”
Section: Psychological and Social Protective Factorsmentioning
confidence: 99%
“…46,47 For example, a qualitative study investigating experiences of a first episode of psychosis identified two key themes, namely tenacity, which required long-term effort, and rebounding. 48 Additional resources such as determination and support from others were described as resilience mechanisms. 48 The results of that study identify a potential mechanism of effortful tenacity, bouncing back and social support.…”
Section: Main Findingsmentioning
confidence: 99%